Analisis Faktor-Faktor yang Mempengaruhi Kepatuhan Wajib Pajak E-Commerce di Kota Medan - Dewi, Togap Intan Sri; Sebayang, Minda Muliana; Lores, Linda (Universitas Syiah Kuala, 2025)
The development of e-commerce in Indonesia grows rapidly, so it is expected to increase the potential tax that will be obtained by the country. However, tax compliance is a challenge, especially because Indonesia implements a self-assessment system to collect taxes, where taxpayers calculate, pay, and report their own taxes. As per attribution theory, e-commerce tax compliance can be caused by both internal and external factors. Therefore, a study was conducted with an associative approach, to analyze several factors that affect e-commerce taxpayer compliance. This study is a quantitative research, using primary data, namely by distributing questionnaires to as many as 90 respondents. Sampling was carried out using a purposive sampling approach from 735 e-commerce sellers in Medan City, which are the population in this study. The data was processed using Microsoft Excel and SPSS apps, and analyzed by multiple linear regression tests. The results of this study show that Tax Knowledge, Taxpayer Awareness, Tax Counseling, Tax Rates, and Tax Sanctions partially and simultaneously have an influence on E-commerce Taxpayer Compliance in Medan City.